COVID 19 with Cardiac Injury Complication, A case Report - Puti Sarah Saus; Dicky Hanafy; Rossana Barack (Jurnal Kardiologi Indonesia, 2020)
Background : The Corona virus Disease COVID-19 have been independently associated with the cause of pneumonia and acute respiratory distress syndrome with high risk of mortality. Mounting evidence substantiates the presence of cardiac injury in patients with COVID-19. Although a recent study reported that 12% of patients had COVID-19 associated acute cardiac injury. Case presentation : A 38 year old male was admitted with pneumonia and cardiac symptoms. He was genetically confirmed as COVID-19 by swab PCR testing, 1 week after admission. He also had elevated CKMB and Hs troponin T level, high Ferritin level, CRP, lymphopenia, and a slight increase in N/L ratio. Chest radiography showed bilateral pneumonia. The patient was confirmed to the diagnosis of Myocardial injury. After receiving tocilizumab and immunoglobulin, his condition improved gradually with the declining laboratory inflammation marker, but there was a secondary infection with an increased of leucocyte and worsen chest radiography, escalating antibiotic and metilprednisolon was given, the patient gradually improving. Conclusion : COVID-19 patients may develop cardiac complication such as cardiac injury or myocarditis, and this is our first case of COVID-19 infection complicated with cardiac injury.